Diversification Rates and the Evolution of Species Range Size Frequency Distribution - Castiglione, Silvia; Mondanaro, Alessandro; Melchionna, Marina; Serio, Carmela; Di Febbraro, Mirko; Carotenuto, Francesco; Raia, Pasquale (Frontiers in Ecology and Evolution, 2017)
The geographic range sizes frequency distribution (RFD) within clades is typically right-skewed with untransformed data, and bell-shaped or slightly left-skewed under the log-transformation. This means that most species within clades occupy diminutive ranges, whereas just a few species are truly widespread. A number of ecological and evolutionary explanations have been proposed to account for this pattern. Among the latter, much attention has been given to the issue of how extinction and speciation probabilities influence RFD. Numerous accounts now convincingly demonstrate that extinction rate decreases with range size, both in living and extinct taxa. The relationship between range size and speciation rate, though, is much less obvious, with either small or large ranged species being proposed to originate more daughter taxa. Herein, we used a large fossil database including twenty-one animal clades and more than 80,000 fossil occurrences distributed over more than 400 million years of marine metazoans (exclusive of vertebrates) evolution, to test the relationship between extinction rate, speciation rate, and range size. As expected, we found that extinction rate almost linearly decreases with range size. In contrast, speciation rate peaks at the large (but not the largest) end of the range size spectrum. This is consistent with the peripheral isolation mode of allopatric speciation being the main mechanism of species origination. The huge variation in phylogeny, fossilization potential, time of fossilization, and the overarching effect of mass extinctions suggest caution must be posed at generalizing our results, as individual clades may deviate significantly from the general pattern.